Biophysical and chemical handles to control the size of DNA nanoparticles produced by rolling circle amplification. (27th July 2016) - Lee, So Yeon; Kim, Kyoung-Ran; Bang, Duhee; Bae, Se Won; Kim, Hak Joong; Ahn, Dae-Ro
Abstract : The size of DNA nanoparticles produced by rolling circle amplification (RCA) can be controlled by incorporation of structure-forming sequences and amine-modified nucleotides in the replication part. Abstract : Although rolling circle amplification (RCA) is an efficient method to produce DNA materials for biomedical applications, it does not yield nano-sized products suitable for intracellular delivery. We here provide the ways to control the size of RCA products and show a potential application of the size-controlled DNA nanoparticles.